THE ROLE OF UNIVERSAL AND SCIENTIFIC VALUES IN THE SPIRITUAL DEVELOPMENT OF FUTURE TEACHERS - Kamolova, Shirin (Журнал Педагогики и психологии в современном образовании, 2021)
This article also discusses the importance of universal and scientific values in shaping the scientific outlook of future teachers. The essence of the content of universal values is scientifically illuminated.